Factors affect adaptive performance among officers at Universiti Malaysia Perlis (UniMAP) - Zauyah, Mustafa (2021)
The purpose of the research was to study factors that affect adaptive performance on firm performance at Universiti Malaysia Perlis (UniMAP). Today's organizations are dealing with a dynamically changing environment where individuals need to adapt to an ever-changing work environment. Adaptive performance refers to the adaptability and capability of an individual to solve problems with creatively and change behaviours to meet the demands of a new complex environment to cope with the rapid and uncertain changes in a new era of technology and culture. The independent variables in this study include improvisational bricolage, self-efficacy, perceived organisational support and work autonomy. This quantitative research was conducted through a survey method among officers at Universiti Malaysia Perlis (UniMAP). There were four hypotheses of the study, and the results showed that only two of the dependent variables were accepted (improvisational bricolage and self-efficacy) and another two variables were rejected. This study also presented the implications for theories and practices, specifically on the adaptive performance among UniMAP officers. Future research was suggested to explore the importance of adaptive performance among individuals in organization.